Morphometric variation among 28 sub-populations of Barbodes binotatus in Indonesia - Septiana Sri Astuti,; Anik Martinah Hariati,; Kusuma, Wahyu Endra; Wiadnya, Dewa Gede Raka (Penerbit Universiti Kebangsaan Malaysia, 2022)
Morphological variability-based truss morphometry analysis is often used to identify fish population, morphometric asymmetry, and evolutionary changes of fishes. This study aims to analyze the level of symmetry and asymmetry of Barbodes binotatus from several sampling areas in terms of geographic distribution variability in Indonesia, such as Java, Bali, Nusa Tenggara, Sumatera, Kalimantan and Sulawesi. A total of 845 samples were collected from 28 sampling areas. Digital imaging and landmark points were analyzed using the tpsDig.2 program. The parameters including standard landmarks, truss morphometry and geometric-morphometric analysis were completed using SAGE software in order to identify the symmetry-asymmetry level of fishes from each location. Results showed a highly asymmetry level (P<0.0001) in procrustes ANOVA with three factors analyzed: Individual analysis, side identification, and interactions of individual and side. The asymmetry levels of B. binotatus were varied within areas, which recorded at 65.31% for Java Island, 50.16% for Nusa Tenggara, 67.12% for Bali, 67.12% for Sumatera, 30.15% for Kalimantan, and 30.17% for Sulawesi. The asymmetry level of B. binotatus in four major regions (Java, Nusa Tenggara, Bali, and Sumatra) was significantly higher (P<0.0001), while other areas in Kalimantan and Sulawesi tend to be lower than others (P>0.0001). Further research with a genetic approach is needed to identify genetic populations and prove the existence of genetic factors that affect the level of asymmetry in individual body shape.